Models of surface complexing for a quantitative description of adsorption interactions of biomolecules with high disperse silica - Vlasova, N. N.; Golovkova, L. P.; Markitan, O. V.; Severinovskaya, O. V.; Stukalina, N. G.; Chuiko, A. A. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2006)
Surface complexation model which explains adsorption in terms of chemical reactions between surface functional groups and dissolved chemical compounds, is reported as an alternative for empirical approach to describing adsorption of biomolecules at oxide/water interface. The use of surface complexation model is demonstrated for adsorption of bilirubin, bile acids, amino acids, and biogenic amines from aqueous solution at high disperse silica surface. It is shown that these organic molecules are adsorbed due to formation of outer-sphere complexes as a result of interaction between silanol groups of silica surface and functional groups of biomolecules.